Pengaruh NPL, LDR, dan CAR Terhadap Profitabilitas dengan CKPN sebagai Variabel Moderasi - Nikmah, Balqis Nurul; Gurendrawati, Etty; Susanti, Santi (LPPM Universitas Negeri Jakarta, 2023)
This study aims to see the effect of non-performing loans, loan to deposit ratio and capital adequacy ratio on profitability with allowance for impairment losses as a moderating variable. The population in this study are banking companies listed on the IDX in 2020-2021. 66 data samples were selected after selecting the sample by purposive sampling method. This study used the panel data regression analysis technique which was processed using the Eviews 11 application with the selected regression model being the fixed effect model. The results of the study show that partially non-performing loans, loan to deposit ratios, and capital adequacy ratios have an effect on profitability. Allowance for impairment losses is able to moderate the effect of non-performing loans on profitability. Allowance for impairment losses is unable to moderate the effect of the loan to deposit ratio and capital adequacy ratio on profitability.